2009
DOI: 10.1002/jobm.200900124
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antibiotic resistant E. coli and Enterococcus spp. in stool of healthy growing children in Portugal

Abstract: From stool specimens of 118 healthy children's (1-14 years) in Portugal 92 E. coli and 101 Enterococcu s spp. strains have been isolated. Almost half (40.2%) of the E. coli isolates were resistant to ampicillin, 25.0% were resistant to tetracycline and 26.1% were resistant to streptomycin. Resistance genes detected by specific PCR included bla(TEM) and/or bla(SHV) and/or bla(CTX-M) (33 of 37 ampicillin and/or cefotaxime resistant isolates), tet (A) and/or tet (B) (16 of 23 tetracycline-resistant isolates), aad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
3
18
1
Order By: Relevance
“…In this study, E. faecium was the most dominant species with prevalence of 55.4%. This finding is consistent with studies that have established the preponderance of E. faecium in healthy human samples with 44.9% E. faecium and 34.7% E. faecalis (Barreto et al 2009). A similar distribution of enterococcal species was observed in poultry (Krocko et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, E. faecium was the most dominant species with prevalence of 55.4%. This finding is consistent with studies that have established the preponderance of E. faecium in healthy human samples with 44.9% E. faecium and 34.7% E. faecalis (Barreto et al 2009). A similar distribution of enterococcal species was observed in poultry (Krocko et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…At present, STRresistant isolates have been identified in many other important pathogens, such as Shigella flexneri, Vibrio cholerae, Pseudomonas aeruginosa, and even in commensal E. coli sampled from healthy individuals (32)(33)(34)(35). A high resistance incidence to this drug is frequently due to point mutations in rpsL gene, with the most common mutations occurring at the codons K43 and K88 (36) that were examined here.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier reports have shown that the ermB erythromycin-resistant gene is the most frequently resistance gene found among erythromycin-resistant enterococci tested [39].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%